Managing Rural Tourism in Corsica: How to Move from Competition to Complementarity. Discussion on the LEADER Program - Caroline Tafani (Revue de Géographie Alpine)
In Corsica, rural tourism is a fragmented competence, supported by institutions in charge of agriculture and rurality as well as tourism. A cross-sectoral and multi-actor sector by nature, but also an economic field known for the atomicity of its offer, rural tourism is today the focal point of the development strategies carried out by the Local Action Groups in the framework of the LEADER programme. Thus, if, over and above the competition between institutions and the division between them, LEADER takes up the issue of tourism development in its areas of action, we can expect the programme to act as a rallying point for local initiatives and to encourage the emergence of an innovative, structured and legible offer for the destination. It is through a descriptive and empirical study that we discuss here the management of rural tourism in Corsica with a specific focus on the role of the LEADER programme as a socio-spatial integrator of dispersed strategies.